Pharmacognostical Studies on Inflorescences of Aerva pseudotomantosa Blatt & Hallb - Sharma, Mahesh C. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Aerva pseudotomantosa Blatt & Hallb (family amaranthaceae) is a plant of desert region. It is commonly known as bui and buari. It is herb or subshrub; Stem erect, stoloniferous or climbing, leaves alternate or opposite, margin entire, flowers perfect, unisexual or dioecious, small or very small. Inflorescences are spikes, terminal or axillary, simple or in complex thyrsoid structures. Bracts and bracteoles are membranous, persistent or bracteoles falling off with perianth in fruit. Tepals are 4 or 5, ovate or oblong, membranous or papery, lanose, with only 1 vein. Stamens are 4 or 5; filaments subulate, unequal, united to short cup at base, alternating with pseudostaminodes, pseudostaminodes subulate to oblong; anthers 2-loculed. Ovary is obovoid or subglobose, glabrous; style persistent; stigmas 2, capitate. Utricles ovoid, compressed, membranous, indehiscent or irregularly dehiscent (bursting), falling off with perianth. Seeds are reniform-orbicular, lenticular, compressed. Traditionally, the whole plant extract is widely used by various tribal communities, forest dwellers and in desert region for the treatment of variety of ailments such as in gastric complaints, in pain relief, in rheumatism and various venereal diseases. The present paper deals with comprehensive pharmacognostical studies on inflorescences part of this plant, including macroscopical analysis, preliminary examination of inflorescences powder, florescence analysis. This will help in the identification of powder drug prior using in any herbal formulations.